2019
DOI: 10.1186/s13148-019-0641-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chemotherapy for breast cancer on leukocyte DNA methylation landscape and cognitive function: a prospective study

Abstract: Background: Little is known about the effects of chemotherapeutic drugs on DNA methylation status of leukocytes, which may be predictive of treatment benefits and toxicities. Based on a prospective national study, we characterize the changes in leukocyte DNA methylome from pre-to post-chemotherapy (approximately 4 months apart) in 93 patients treated for early stage breast cancer and 48 matched non-cancer controls. We further examined significant methylation changes with perceived cognitive impairment, a clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 30 publications
1
68
0
Order By: Relevance
“…While chemotherapy profoundly impacts DNA methylation landscape in cancer patients [20,21], resistance to treatment continues to be a major obstacle for the success of cancer therapy. In our study, increased in the CpG site methylation levels among responders were all mapped to CpG islands including CDC25B, WBSCR27, ADNP, NEK9, COQ2, SOX5, ACPL2, RBM15, TLE2, RB1CC1 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…While chemotherapy profoundly impacts DNA methylation landscape in cancer patients [20,21], resistance to treatment continues to be a major obstacle for the success of cancer therapy. In our study, increased in the CpG site methylation levels among responders were all mapped to CpG islands including CDC25B, WBSCR27, ADNP, NEK9, COQ2, SOX5, ACPL2, RBM15, TLE2, RB1CC1 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…With regards to clinical heterogeneity, only 20.5% (9/44) of our enrolled articles mentioned the presence or absence of preoperative treatment [38,40,41,45,47,50,53,55]. Some studies suggested that both radiotherapy and chemotherapy can alter a patient's DNA methylation status; therefore, the type of preoperative treatment performed should be clari ed [87,88]. Moreover, four studies investigated the relationship between RASSF1A hypermethylation in peripheral blood and the risk of HCC, and the diagnosis of HCC was con rmed by imaging techniques and serum AFP levels, rather than through pathological examination [56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…With regards to clinical heterogeneity, only 20.5% (9/44) of our enrolled articles mentioned the presence or absence of preoperative treatment [38,40,41,45,47,50,53,55]. Some studies suggested that both radiotherapy and chemotherapy can alter a patient's DNA methylation status; therefore, the type of preoperative treatment performed should be clari ed [83,84]. Moreover, four studies investigated the relationship between RASSF1A hypermethylation in peripheral blood and the risk of HCC, and the diagnosis of HCC was con rmed by imaging techniques and serum AFP levels, rather than through pathological examination [56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%